2008
DOI: 10.1175/2008bams2332.1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Differences in Aircraft and Radiosonde Temperatures

Abstract: Automated aircraft temperatures exhibit considerable variance with aircraft models and on average they are warmerthan radiosonde temperatures; therefore, field studies and bias corrections for NWP models are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 21 publications
(18 reference statements)
6
63
0
Order By: Relevance
“…The results indicate that AMDAR temperatures are 0.328C colder than radiosonde observations. However, the earlier studies (Zhu et al 2015;Ballish and Kumar 2008;Benjamin and Moninger 2016) indicated that aircraft temperature observations are on average warmer than radiosonde observations. This difference will be discussed below.…”
Section: ) Overall Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The results indicate that AMDAR temperatures are 0.328C colder than radiosonde observations. However, the earlier studies (Zhu et al 2015;Ballish and Kumar 2008;Benjamin and Moninger 2016) indicated that aircraft temperature observations are on average warmer than radiosonde observations. This difference will be discussed below.…”
Section: ) Overall Resultsmentioning
confidence: 92%
“…results given by Benjamin and Moninger (2016), who show that the biases of U.S. aircraft from rawinsonde are negative near the surface and then become positive in the mid-to upper troposphere (600-150 hPa). Benjamin and Moninger (2016) have summarized other research results (Zhu et al 2015;Ballish and Kumar 2008) that indicated that aircraft temperature observations are on average warmer than radiosonde observations in the upper troposphere.…”
Section: ) Rmsd Dependence On Separationmentioning
confidence: 90%
See 1 more Smart Citation
“…Ballish and Kumar (2008) showed that the temperatures from passenger aircraft are warm-biased at cruise altitude (200-300 hPa). This has not been accounted for in ERA-I.…”
Section: Possible Sources Of the Differing Temperature Trendsmentioning
confidence: 99%
“…Petersen (2016) showed that at flight level the errors of temperature and wind in the 3-48 h forecast were reduced by nearly 50 % when assimilating data from passenger aircraft. However, Ballish and Kumar (2008) and Drüe et al (2008) identified that the AMDAR aircraft temperature is strongly affected by a warm bias, which can fluctuate by altitude, aircraft type, and phase of flight, while the reason for this bias is not fully understood (Ingleby et al, 2016).…”
Section: Introductionmentioning
confidence: 99%